Implemented myeloma management with whole-body low-dose CT scan: a real life experience. Issue 7 (2nd July 2016) - Mangiacavalli, Silvia; Pezzatti, Sara; Rossini, Fausto; Doni, Elisa; Cocito, Federica; Bolis, Silvia; Corso, Alessandro
Abstract: A total of 318 consecutive myeloma patients underwent whole-body low-dose CT scan (WBLDCT) at baseline and during follow-up as a radiological assessment of lytic lesions in place of skeletal X-ray survey. After WBLDCT baseline assessment, 60% had bone involvement. The presence of lytic lesions represented the only met CRAB (hyperCalcaemia, Renal insufficiency, Anaemia, Bone lesions) criteria in 29% of patients. Patients presenting with extramedullary masses were 10%. Radiological progression was documented in 9% of the population with available follow-up. Additional pathological incidental findings were detected in 28 patients (14.5%), most located in the chest region (68%). In conclusion, our real-life data shows that WBLDCT scan represents a reliable imaging tool for decision-making process for multiple myeloma management in different disease phases, providing significant additional information on the presence of soft tissues plasmacytomas detection as well as the presence of pathological incidental findings.